2019
DOI: 10.1186/s41182-019-0166-5
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Wuchereria bancrofti infection by anti-filarial IgG4 in urine among schoolchildren and molecular xenomonitoring in Sri Lanka: a post mass drug administration study

Abstract: Background Surveillance of hidden foci or resurgence of the bancroftian filariasis has high priority to maintain the elimination status in Sri Lanka. For the surveillance, two methods were applied in Matotagama, Matara, Sri Lanka; (i) molecular xenomonitoring (MX) by PCR to detect parasite DNA in the vector, Culex ( Cx ) quinquefasciatus and (ii) survey of anti-filarial IgG4 in urine samples from schoolchildren. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
2
0
3
Order By: Relevance
“…Moreover, an effective surveillance system is essential for WHO validation/certification of VL elimination. Towards addressing such endgame challenges, an index-based surveillance approach has been proposed and implemented in endemic settings for lymphatic filariasis (LF) together with an intervention package to curb transmission [33][34]. Moreover, previous study, that implemented an index-based approach to explore the association between asymptomatic VL infection with post-kala-azar dermal leishmaniasis (PKDL) patients, provided further evidence to support this pragmatic approach for gauging residual infection since VL/PKDL transmission is highly clustered [35].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an effective surveillance system is essential for WHO validation/certification of VL elimination. Towards addressing such endgame challenges, an index-based surveillance approach has been proposed and implemented in endemic settings for lymphatic filariasis (LF) together with an intervention package to curb transmission [33][34]. Moreover, previous study, that implemented an index-based approach to explore the association between asymptomatic VL infection with post-kala-azar dermal leishmaniasis (PKDL) patients, provided further evidence to support this pragmatic approach for gauging residual infection since VL/PKDL transmission is highly clustered [35].…”
Section: Discussionmentioning
confidence: 99%
“…8 Hasil negatif ini dapat disebabkan oleh keberhasilan program MDA, 16,17 kadar antigen yang rendah pada desa dengan transmisi penularan rendah 8 dan faktor musim. 18 Rendahnya transmisi penularan berhubungan dengan keberadaan larva filaria di dalam tubuh vektor. 19 Kemampuan bertahan hidup larva filaria menjadi bentuk infektif di dalam tubuh vektor dipengaruhi oleh kemampuan bertahan hidup dan perilaku nyamuk vektor.…”
Section: Hasilunclassified
“…Penelusuran penularan dan kondisi kejadian filariasis di daerah endemis, akan lebih baik jika mengidentifikasi keberadaan antibodi filaria, dan penelusuran filaria pada tubuh vektor. 18 Sebuah penelitian di Sri Lanka menunjukkan bahwa untuk mendeteksi filaria di dalam tubuh manusia dapat menggunakan kombinasi pemeriksaan antibodi di dalam urin dan xenomonitoring larva filaria pada vektor. 18 Metode tersebut baik untuk diimplementasikan terkait faktor penularan filariasis yang komplek.…”
Section: Hasilunclassified
See 1 more Smart Citation
“…As an example, individuals within areas having undergone mass administration with albendazole for the treatment of ascariasis may have indeed cleared any infection, however, any diagnostic assay targeting anti- Ascaris antibodies used to assess these individuals may remain positive (Jourdan et al ., 2018). In areas where disease elimination is sought, it has been suggested that antibody-targeting assays may be appropriate for use with young children who have not yet received treatment as a means of assessing whether the transmission is still taking place (Jourdan et al ., 2018; Takagi et al ., 2019). In doing so, seroconversion rate, typically somewhere between at least 4 and 8 weeks after initial exposure, must be taken into consideration (van Grootveld et al ., 2018; Vlaminck et al ., 2019).…”
Section: Detection Of Anti-helminth Urine-antibodiesmentioning
confidence: 99%